Emergence of multiple fluorophores in individual cesium lead bromide nanocrystals - Yuhai Zhang (Nature Portfolio, 2019)
Inorganic perovskite nanocrystals attract lots of research attention but the origin of their photoluminescence remains debatable. Here Zhang et al. show that behavior of both CsPbBr3 and Cs4PbBr6 nanocrystals is like individual molecular fluorophores and independent of the structural dimensionalities.